Moving beyond stewardship to partnership with nature: how Swiss alpine farmers’ relationships to nature and relational values are co-constituted - Mollie Chapman; Anna Deplazes-Zemp (Ecosystems and People)
Ecologically considerate use of nature (including agriculture) has often been associated with ‘stewardship’ as a human-nature relationship which involves human care, responsibility and accountability and is thus more sustainable than the alternative human-nature relationship of manager of nature. We show that the consideration of nature in agriculture can go further than stewardship by presenting data from qualitative interviews with Swiss Alpine farmers indicating that many of them view their relationship with nature as a form of partnership. Drawing on literature of human-nature partnership, we characterize this relationship by 1) bidirectionality – a give and take between nature and humans–, 2) the understanding of nature as a subject rather than an object and 3) interaction with nature that consists of collaboration rather than giving commands. The mountain farmers expressed all of these features in their farming practices and descriptions of their role in nature. A few farmers even saw their role as subordinates to nature, for which we introduced the new human-nature relationship category of “apprenticeship”. We further suggest that the partnership relation between humans and nature in many respects shares key features with relational values, for instance in its non-centric nature and in its emphasis of the combination of benefits for people with care for nature. In that sense, we aim at combining different accounts of inclusive, non-dichotomous and context-sensitive dealings with nature and we suggest that this combination is applicable also to contexts beyond agriculture.